Chloroflexota in agricultural soils: current knowledge and future research directions - Dobrzyński, Jakub; Gradowski, Marcin; Radkowski, Adam; Bujak, Henryk (Frontiers in Microbiology, 2026)
The review organizes current knowledge on the biofunctions, life-history strategies, and environmental responses of Chloroflexota in agricultural soils. Members of this phylum play key roles in carbon, nitrogen, and phosphorus cycling through a high degree of metabolic versatility, including photosynthesis, redox reactions, and the degradation of complex organic compounds such as cellulose and lignin. Chloroflexota contribute to major soil processes, including nitrification, denitrification, and nitrogen fixation. In agricultural soils, the predominant classes are Anaerolineae and Ktedonobacteria, each exhibiting distinct ecological strategies. Anaerolineae members, such as Leptolinea, Bellilinea, and Anaerolinea, are often associated with nutrient-enriched conditions, suggesting copiotrophic or competitor- and ruderal-like traits. In contrast, Ktedonobacteria show negative responses to increased soil carbon and nitrogen, suggesting that its members are oligotrophic. Despite these trends, responses to soil organic carbon, nitrogen, phosphorus, and pH vary substantially across studies, likely due to functional heterogeneity within the phylum and insufficient taxonomic resolution in metataxonomic datasets. Emerging evidence from metagenome-assembled genomes (MAGs) reveals that Chloroflexota harbor genes involved in carbon fixation, nitrogen transformations, and phosphorus solubilization, highlighting their previously underestimated ecological significance. However, most Chloroflexota remain uncultured, and available genomic data are still limited. Future research integrating high-resolution taxonomic profiling, metagenomics, and cultivation-based approaches is needed to clarify the ecological roles and life-history strategies of Chloroflexota members. Such advances may ultimately establish this phylum as an important microbial indicator of soil fertility and environmental change in agricultural soils.